Value and Price of Russian Business: The Entity, the Relationship and Impact of Financial Indicators - Irina, Kosorukova; Svetlana, Plyasova; Nikolay, Prokimnov; Alexander, Rodin (Journal of Reviews on Global Economics, 2018)
Topicality: In the article the authors analyze the relationship between the book and market value and the price (level of capitalization) of the business, and also analyze the nature of the relationship of these indicators with the traditional financial ratios. The purpose of the article is to determine the state of these relations in the modern economy of Russia. Practical Usefulness: Determination of materiality influence of financial coefficients which used in traditional financial analysis on value and price of business that gives the chance of forecasting of development and decision-making within management of business` value, and also more effective investment of means in securities. Novelty: In modern Russian economic conditions, only part of the traditional financial ratios has an impact on the prices and business value. The analysis presented in the article indicates the feasibility of forming such a system of indicators, which is more informative in terms of their use for the implementation of value-based analysis and approach for decision-making in the organization.